Upshot of Open Lateral Internal Sphincterotomy And Arkaksharsutra (caustic therapy) In the Treatment of Fissure-In-Ano W.S.R To Fissure in ano: One Centre Experience - Sudesh, Gupta; Aarushi, Prasher (International Research Journal of Ayurveda & Yoga, 2021)
Background: The word Fissure in ano as a whole means “to cut circumferentially” or to cut all around. Fissure in ano resembles fissure-in-ano which is amongst the common painful condition occuring in the anorectal region. Ksharasutra (Caustic therapy) is a parasurgical procedure effective in the management of Fissure in ano. Aim: To compare the efficacy of Arka Ksharasutra (Caustic therapy) and open lateral internal sphincterotomy (OLIS) in the management of Fissure in ano. Methodology: Total 30 patients having signs and symptoms of fissure-in-ano were selected and randomly divided into two groups. In Group A (n=15), Arka Ksharasutra (Caustic therapy) ligation after anal stretching was carried out while in Group B (n=15), OLIS with excision of skin tag was carried out under local anesthesia or spinal anesthesia. Relief in postoperative symptoms and complications (if any) were recorded for 4 weeks and follow-up was done for 1 month. Results: In both the groups, significant results were obtained, but the difference among groups was statistically insignificant. Duration required for postoperative symptoms like pain, bleeding, swelling and wound healing to subside was found to be more in Group A(Ksharsutra (Caustic therapy) than Group B (OLIS). Conclusion: Open lateral internal sphincterotomy (OLIS) provided better results than Ksharasutra (Caustic therapy) ligation in the management of Fissure in ano.